2008
DOI: 10.1186/1755-8794-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide SNP comparative analysis between EGFR and KRAS mutated NSCLC and characterization of two models of oncogenic cooperation in non-small cell lung carcinoma

Abstract: Background: Lung cancer with EGFR mutation was shown to be a specific clinical entity. In order to better understand the biology behind this disease we used a genome wide characterization of loss of heterozygosity and amplification by Single Nucleotide Polymorphism (SNP) Array analysis to point out chromosome segments linked to EGFR mutations. To do so, we compared genetic profiles between EGFR mutated adenocarcinomas (ADC) and KRAS mutated ADC from 24 women with localized lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 31 publications
5
32
0
1
Order By: Relevance
“…Homozygous deletion was seen only at 9p21.3 including CDKN2A and limited to EGFR -mutated tumours among ALK fusion-negative neoplasms as reported in the literature [44] and also seen in ALK -fusion positive ones . That deletion of 9p23-24.1 and 13q14.2 including tumour suppressor genes was rare in ALK fusion-positive tumours suggests that they can grow even if the functions of these suppressor genes are retained.…”
Section: Discussionmentioning
confidence: 71%
“…Homozygous deletion was seen only at 9p21.3 including CDKN2A and limited to EGFR -mutated tumours among ALK fusion-negative neoplasms as reported in the literature [44] and also seen in ALK -fusion positive ones . That deletion of 9p23-24.1 and 13q14.2 including tumour suppressor genes was rare in ALK fusion-positive tumours suggests that they can grow even if the functions of these suppressor genes are retained.…”
Section: Discussionmentioning
confidence: 71%
“…The ATM missense p.F858L is known to impact the interaction of ATM with beta-adaptin, which is necessary for clatherin mediated receptor endocytosis and is proposed to contribute to the hereditary radio sensitivity and breast cancer3738. In addition to breast cancer-associated variants, a missense substitution in STK11 , p.H175Y, previously reported in a lung carcinoma39 was been found in one patient. One non-TNBC patient carried simultaneously pathogenic variants in BRCA1 and ATM .…”
Section: Resultsmentioning
confidence: 85%
“…Prognostic markers have not been specifically studied in EGFR mutated cancers and could help classify this new entity [3]. In a previous work, using SNP array, we showed that tumors with EGFR mutations had a copy number increase of a region on chromosome 7 (7p21.1-7p15.3) encompassing the TWIST1 gene, a highly conserved basic helix-loop-helix transcription factor regulator of embryogenesis [4]. This was confirmed on CGH arrays with 40% of EGFR mutated tumors showing copy number increase of this region.…”
Section: Introductionmentioning
confidence: 96%